(untitled) (Filologia e Linguística Portuguesa, 2005)
This article deals with phenomena of the phonetic transposition (methatesis and hiphertesis) presented in manuscripts of century XVIII. Through examples - data that were removed from documents dated between the years 1731 and 1782 - it is shown the phenomenon of transposition in the evolution of Portuguese Language.